Facilities for Education at VNU National Defense and Security Training Center - Thi Hong Thanh, Vuong; Hien, Le Thi; Hoai, Trinh Thi Thu; Thinh, Pham Duc (VNU Journal of Science: Education Research; Vol 39 No 1SDO - 10.25073/2588-1159/vnuer.4845, 2023)
Facilities for education play an important role in the training quality of educational institutions. Good educational facilities will help teachers innovate teaching methods and help learners better absorb knowledge. This study was conducted to analyze the current situation of educational facilities at VNU-National Defense and SecurityTraining Center and to analyze the influence of facilities on the training quality of the Center so as to give orientations for the development of the Center's educational facilities. Through the quantitative research method with a sample of 250 students attending national defense and security education at VNU-National Defense and SecurityTraining Center, the research results show that the educational facilities factor has a positive influence and explains 25,1% of the variation of training quality besides the elements of training programs, lecturers and students.